EVALUATION OF IRON SUPPLEMENTATION PROGRAM FOR PREGNANT WOMEN IN GUNUNGKIDUL, INDONESIA, 2015 (Proceedings of the International Conference on Public Health, 2017)
Iron supplementation program aims to prevent anemia during pregnancy. Anemia among pregnant women is a risk of miscarriage, premature birth, low birth weight (LBW) and postpartum hemorrhage. The anemia prevalence in Gunungkidul increased from 14.97% in 2014 to 21.88% in 2015. This study aimed to evaluate iron supplementation program for pregnant women in Gunungkidul in 2015. This was a descriptive study involving staff from 30 Public Health Centers (PHC) and Gunungkidul District Health Office (DHO). Data on program resources, planning, implementation and monitoring evaluation were collected using structured questionnaires and checklist sheets. Data on program coverage and anemia prevalence were taken from DHO’s reports. There was 62 staff (midwives and nutritionist) working in the program. The number of the estimated pregnant women and iron supplementation needed were calculated at DHO level. Iron supplementation administration was conducted at PHC level, involving midwives, nutritionists, and pharmacists. Iron supplementation coverage was 88.77%, however, the prevalence of anemia was high (21.88%). Furthermore, most midwives and nutritionist could not ascertain whether the administered iron supplementation was actually consumed by pregnant women. Iron supplementation program in Gunungkidul District needs to put efforts to ascertain treatment adherence.
Keywords: Program Evaluation, Iron Supplementation, Anemia, Pregnant Women